Alterações nos atributos químicos do solo após duas aplicações sucessivas de água residuária de suinocultura - Rossino, Alini Bossolani (2018)
Handling swine manure is a major problem faced by swine farmers in confined systems. One of the possible alternatives for final disposal of swine wastewater (ARS) is its use as a fertilizer because its nutrients can be made available to the plants and may partially or totally supplement the mineral fertilization. In this way, the objective of this study was to evaluate the dynamics of the application of ARS in agroforestry systems in different arrangements and in single pasture, observing the changes of its chemical characteristics over two years of application. The systems were conducted at Fazenda Bonsucesso, located in the municipality of Uberlândia, Brazil, in 2015 and 2016. Three experiments were carried out, one with Urochoa decumbens pasture single, the other with agroforestry systems with Corymbia citriodora in single line and with Corymbia citriodora in line both with pasture between the lines of the tree species. Each experiment was implanted individually, and the systems were compared qualitatively in relation to the system and year. The experimental design was a randomized block design with four replications. The treatments were 5 doses of swine wastewater: 0, 200, 400, 600 and 800 m³ ha-1 year-1. The dynamics of variations of soil chemical attributes in the 0.0-0.20 layers were evaluated; 0.20-0.40 and 0.40-0.60 m depth, comparing the three experiments and two successive applications of ARS (2015 and 2016). The successive applications of ARS provided the soil with nutrient increase in the first year of implantation, mainly in the most superficial layer of the soil. The high levels of Na found indicate that the soil initially had a salinity level considered as saline or saline-sodium, and the observed levels could not be attributed to the experimental period alone. The increase of Ca was discrete and can be explained by the low amount of Ca in ARS. There was a decrease in nutrients Na, Mg, K, P, Zn and Cu after the second year of implantation, which shows that the extraction rates were higher than the amount of nutrients applied to the soil by ARS. The pH of the studied soil was practically unchanged with the application of ARS. The values of base sum and cation exchange capacity (CTC) at pH 7.0, mainly in the simple line arrangement, increased with the application of ARS. The values found for Al and saturation by Al are mostly above that suitable for the main agricultural crops, with an increase in the values from the first to the second year in the simple line arrangement. The highest values of effective CEC were found in the lower soil layer, due to the high content of Al and Na. In general, it is verified that more than the definition of standardized doses should always have the application monitored, in order to keep the contents within the standards consolidated by the reference bulletins of the soil attributes.